Studi Distribusi Pemasaran Hasil Perikanan Laut dari Pelabuhan Ratu, Sukabumi, Jawa Barat - Wawan Okatriza; Achmad Fahrudin; Istiqlaliyah Muflikhati; Yatri I Kusumastuti; Heri Antoni (Buletin Ekonomi Perikanan, 1996)
Fisheries product from Pelabuhan Ratu is distributed through several marketing institutions. The marketing institutions involved are fisherman, bakul pengumpul, bakul pengolah, bakul pengecer, wholesaler, retailer and institutional market. Areas of the merketing are Pelabuhan Ratu, Sukabumi, Bogor, Bandung and Jakarta. The Retailer gets the marketing margin more than other institutions. The structure of marketing cost is different at each institution, however in general, the cost consist of TPI fee, market fee, transportation cost, water and ice cost, packing cost and labor cost. The average of the fisherman's share for the fish products that are marketed in Pelabuhan Ratu area is 68,65 %, and for outside areas is 59,96 %.